The Role of Environmental Disclosure in Mediating Independent Commissioners and Environmental Costs on Profitability - dhela septian anggaretta; Siti Anisyah; Amin Pujiati; Sucihatiningsih Dian Wisika Prajanti (Postgraduate Program Merdeka University, 2024)
This study aims to determine the effect of the independent board of commissioners and environmental costs on profitability through environmental disclosure either directly or indirectly in construction industry companies listed on the Indonesia Stock Exchange. This research is quantitative descriptive research. The sample de-termination process in this study used a purposive sampling method with a total sample of 20 construction industries during 2021-2022. The results of this study indicate that there is no effect of independent board of commissioners on profitability, there is no effect of environmental costs on profitability, there is no effect of environmental disclosure on profitability, there is an effect of independent board of commissioners on environmental disclosure, there is no effect of environmental costs on environmental disclosure, there is no effect of independent board of com-missioners on profitability through environmental disclosure, and there is no effect of environmental costs on profitability through environmental disclosure. Future research is expected to use other independent variables and company sectors. JEL Classification: G38, M14, Q56 DOI: https://doi.org/10.26905/afr.v7i3.12850